Safety profile of intravenous digoxin in Chinese patients with acute heart failure with reduced ejection fraction: a small-scale prospective cohort study - Liu, Xintian; Zhang, Haojie; Cheng, Wenlin; Fan, Qingkun; Lu, Zhibing; Zheng, Xuan; Zhang, Gangcheng (Frontiers in Pharmacology, 2023)
Background: Adverse effects of intravenous digoxin vary from patients and disease status, which should be closely monitored. Aims: To explore the safety profile of intravenous digoxin in acute heart failure with reduced ejection fraction (HFrEF) among Chinese patients. Methods: A clinical prospective, single-center, single-arm, open-label exploratory clinical trial was performed in patients with acute HFrEF at Wuhan Asia Heart Hospital. A fixed dose of 0.5 mg digoxin was used intravenously once per day for three days. The normalized dosage of digoxin (NDD), toxic serum digoxin concentration (SDC), and adverse reactions of intravenous digoxin were recorded. Results: A total of 40 patients were recruited in the study. The SDC increased from 1.03 ± 0.34 ng/ml to 1.95 ± 0.52 ng/ml during treatment. 50% (20/40) patients reached a toxic SDC of 2.0 ng/ml, and toxic effects were seen in 30% (12/40) patients. Estimated glomerular filtration rate (eGFR) < 60 ml/min [HR: 5.269; 95% CI: 1.905 – 14.575, P = 0.001], NDD ≥ 7 μg/kg [HR: 3.028; 95% CI: 1.119 – 8.194, P = 0.029], and ischemic cardiomyopathy [HR: 2.658; 95% CI: 1.025 – 6.894, P = 0.044] were independent risk factors for toxic SDC. Toxic SDC was effectively identified [area under the receiver operating characteristic (ROC) curve = 0.85, P < 0.001] using this model, and patients would have a higher risk of toxicity with more risk factors. Conclusions: Intravenous digoxin of 0.5 mg was safe and effective for initial dose but not suitable for maintenance treatment in Chinese patients with acute HFrEF. Patients who had lower eGFR, received higher NDD, and had ischemic cardiomyopathy should be closely monitored to avoid digoxin toxicity.